2014
DOI: 10.1111/ajt.12558
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Instant Blood-Mediated Inflammatory Reaction in Clinical Autologous Islet Transplantation

Abstract: y These authors contributed equally.A nonspecific inflammatory and thrombotic reaction termed instant blood-mediated inflammatory reaction (IBMIR) has been reported when allogenic or xenogenic islets come into contact with blood. This reaction is known to cause significant loss of transplanted islets. We hypothesized that IBMIR occurs in patients undergoing total pancreatectomy followed by autologous islet transplantation (TP-AIT) and tested this hypothesis in 24 patients and in an in vitro model. Blood sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
149
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(155 citation statements)
references
References 43 publications
3
149
0
1
Order By: Relevance
“…Further examination on the presentation of islets to autologous blood utilizing a miniaturized in vitro tube model resulted in the expression of TF, verified by our previous in vivo findings 22 . Hence, it was evident that IBMIR is an issue in allogenic and xenogenic islet transplantation as well as in autologous islet transplantation.…”
Section: Hurdles Faced During Pancreatic Islet Transplantationsupporting
confidence: 75%
See 2 more Smart Citations
“…Further examination on the presentation of islets to autologous blood utilizing a miniaturized in vitro tube model resulted in the expression of TF, verified by our previous in vivo findings 22 . Hence, it was evident that IBMIR is an issue in allogenic and xenogenic islet transplantation as well as in autologous islet transplantation.…”
Section: Hurdles Faced During Pancreatic Islet Transplantationsupporting
confidence: 75%
“…Compstatin -a complement inhibitor treatment significantly improved the graft survival under in vivo conditions 26 . In contrast, there was no significant impact of complement proteins during IBMIR in clinical autologous islet transplantation 22 .…”
Section: Hurdles Faced During Pancreatic Islet Transplantationmentioning
confidence: 83%
See 1 more Smart Citation
“…The liver as transplantation side is considered to be a major contributor to these low success rates. Inadequate revascularization,5 the large numbers of natural killer T cells in the liver,6 high concentrations of immunosuppressive drugs,7, 8 and the instant blood‐mediated inflammatory reaction9 play a role in islet graft failure after intraportal transplantation. Therefore, a more adequate transplantation site is required for this technology to gain widespread acceptance and practice.…”
Section: Introductionmentioning
confidence: 99%
“…Instant Blood-Mediated Inflammatory Reaction (IBMIR) was previously found to be common in recipient of islet allo-or xenograft, however, recent study showed its incidence in islet autograft as well, indicated by elevated c-peptide and Thrombin-Anti-Thrombin III Complex (TAT) in blood post-operatively. In the case of TP-IAT, the cytokine release leading to IBMIR may have occurred because of the surgery process itself [57]. Despite these chances for failure, TP-IAT has been found to be safe overall, with low mortality, morbidity, and a good rate of achieving insulin independence [58].…”
Section: Spleen and Omentummentioning
confidence: 99%